Nonanastomotic Biliary Strictures After Liver Transplantation. Issue 10 (30th October 2020) - Ito, Takahiro; Botros, Mina; Aziz, Antony; Guorgui, Jacob G.; Agopian, Vatche G.; Farmer, Douglas G.; Busuttil, Ronald W.; Kaldas, Fady M.
Biliary strictures constitute a major source of morbidity and mortality following liver transplantation (LT). However, studies on the impact of nonanastomotic biliary strictures (NABS) on grafts after LT are limited. 649 patients who underwent LT between January 2013 and June 2017 at our center were retrospectively analyzed and 2.6% (n = 17) of the recipients developed NABS following LT. There were no differences between recipients with and without NABS in indication of LT, graft ischemia time, and type of biliary anastomosis. The incidence of post-LT hepatic artery thrombosis (HAT) (odds ratio [OR]: 15.75, P < .001) and the use of livers from donation after cardiac death (DCD) donors (OR: 8.292, P = .004) were identified as independent significant predictors of NABS by multivariate analysis. Graft survival in those with NABS was significantly worse than in patients without NABS (1-, 3-, and 5-years survival: 64.7%, 57.5%, 0%, vs. 89.8%, 84.0%, 76.4%, P < .001). In conclusion, while the incidence of NABS in our study was relatively low compared to previous reports, NABS was still found to be associated with poor graft survival. Special attention should be paid to NABS occurrence in grafts that develop HAT as well as those from DCD donors.